2018
DOI: 10.5465/ambpp.2018.15903abstract
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the Potential of Chatbots in Education: A State-Of-The-Art Analysis

Abstract: Chatbots are becoming a ubiquitous trend in many fields such as medicine, product and service industry, and education. Chatbots are computer programs used to conduct auditory or textual conversations. A growing body of evidence suggests that these programs have the potential to change the way students learn and search for information. Especially in large-scale learning scenarios with more than 100 students per lecturer, chatbots are able to solve the problem of individual student support. However, until now, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
208
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 272 publications
(224 citation statements)
references
References 63 publications
6
208
0
10
Order By: Relevance
“…A comprehensive systematic review of the use of chatbots in education is provided in this recent survey [9]. The authors identify several perspectives for analyzing current research following the theoretical model of Technology-Mediated Learning (TML) [10]: structure (input), learning process (process), and learning outcome (output).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive systematic review of the use of chatbots in education is provided in this recent survey [9]. The authors identify several perspectives for analyzing current research following the theoretical model of Technology-Mediated Learning (TML) [10]: structure (input), learning process (process), and learning outcome (output).…”
Section: Related Workmentioning
confidence: 99%
“…The authors identify several perspectives for analyzing current research following the theoretical model of Technology-Mediated Learning (TML) [10]: structure (input), learning process (process), and learning outcome (output). Regarding the input perspective, several dimensions have been identified [9]: student profile, educational settings, and chatbot technology. Learning outputs depend on individual student characteristics such as personality traits, technological skills, and educational and social background [9].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance student perception and motivation for the assessment of the effectiveness of a course, the third meta-requirement (MR3) focuses on information on the intension and implementation of the course evaluation (e.g., [33]). The fourth meta-requirement (MR4) deals with the need for an individualized CA to be easy accessible, available twenty-four hours a day, and speeds up response times to enhance user satisfaction (e.g., [21]).…”
Section: Step 2: Rigor -Deriving Requirements From Scientific Literaturementioning
confidence: 99%
“…Research on CA support for lecturers is still scarce. Moreover, Winkler and Söllner [21] emphasize that CAs might also have great potential as an evaluation tool for lecturers. In a recent study Kim et al [22] compared a CA against online surveys in an experiment and found that participants using a chatbot were providing more differentiated responses and, thus, the CA survey resulted in higher-quality data compared to the online survey.…”
Section: Introductionmentioning
confidence: 99%